Anatomical and Physiological Differences between Children and Adults Relevant to Traumatic Brain Injury and the Implications for Clinical Assessment and Care - Figaji, Anthony A. (Frontiers in Neurology, 2017)
General and central nervous system anatomy and physiology in children is different to that of adults and this is relevant to traumatic brain injury and spinal cord injury. The controversies and uncertainties in adult neurotrauma are magnified by these differences, the lack of normative data for children, the scarcity of pediatric studies, and inappropriate generalization from adult studies. Cerebral metabolism develops rapidly in the early years, driven by cortical development, synaptogenesis, and rapid myelination, followed by equally dramatic changes in baseline and stimulated cerebral blood flow. Therefore, adult values for cerebral hemodynamics do not apply to children, and children cannot be easily be approached as a homogenous group, especially given the marked changes between birth to age 8. Their cranial and spinal anatomy undergoes many changes, from the presence and disappearance of the fontanels, the presence and closure of cranial sutures, the thickness and pliability of the cranium, anatomy of the vertebra, and the maturity of the cervical ligaments and muscles. Moreover, their systemic anatomy changes over time. The head is relatively large in young children, the airway is easily compromised, the chest is poorly protected, the abdominal organs are large. Physiology changes - blood volume is small by comparison, hypothermia develops easily, intracranial pressure is lower, and blood pressure normograms are considerably different at different ages, with potentially important implications for cerebral perfusion pressure thresholds. Mechanisms and pathologies also differ – diffuse injuries are common in accidental injury, and growing fractures, non-accidental injury and SCIWORA are unique to the pediatric population. Despite these clear differences, and the vulnerability of children, the amount of pediatric-specific data in TBI is surprisingly weak. There are no robust guidelines for even basics aspects of care in children, such as intracranial pressure and cerebral perfusion pressure management. This is particularly alarming given that TBI is a leading cause of death in children. To address this, there is an urgent need for pediatric-specific clinical research. If this goal is to be achieved, any clinician or researcher interested in pediatric neurotrauma must be familiar with its unique pathophysiological characteristics.